The realistic mathematics education approach with the help of liveworksheets on students' critical thinking skills - Iskandar, Rossa; Komala, Elsa; Sugiarni, Rani (Papanda Publisher, 2025)
Critical thinking skills are important for students in mathematics learning, but this ability has not developed optimally in most students. This study aims to determine the achievement and improvement of students' critical thinking skills through the Realistic Mathematics Education (RME) approach assisted by Liveworksheets, as well as to see students' responses to the learning. This study used the Quasi Experimental method with Nonequivalent Comparison Group Design. The study population was students of grades X-1 and X-2 of SMA PGRI Cianjur in the 2024/2025 academic year who were selected by purposive sampling. The experimental class used the RME approach assisted by Liveworksheets, while the control class used conventional learning. Critical thinking ability instruments were found in the SPLTV material and student response questionnaires. Data analysis to see achievement used the difference test of two means while improvement data was analyzed using Mann Whitney and student responses used percentages based on students' positive responses. The results showed that the achievement of students' critical thinking skills with the RME approach assisted by Liveworksheets was better than conventional learning; Meanwhile, the increase in students' critical thinking skills in the experimental class was better than conventional learning and was in the low category and students' attitudes responded positively to learning with the RME approach assisted by Liveworksheets